Pre-Service Teachers’ Perspectives on Teaching Media in Microteaching Classes - lindanatalia, lindanatalia; Utomo, Slamet; Budi Suryani, Fitri (Universitas Jambi, Magister Program of English Education Department, 2025)
Teaching media are essential in microteaching as they help clarify lesson content, foster student engagement, and enhance teaching performance. This study aims to investigate pre-service teachers’ perspectives on the use of teaching media in microteaching classes at the English Education Department of a private university in Indonesia, focusing on their perceptions of the role, challenges, and impact of media use as well as their readiness, strategies, and reflections. Employing a qualitative case study approach, data were collected from 41 seventh-semester students through questionnaires and semi-structured interviews, and then analyzed using coding, categorization, and thematic analysis, with credibility ensured through member checking. The findings reveal that pre-service teachers generally perceive teaching media as valuable tools for improving explanation clarity, capturing students’ attention, and stimulating participation. They reported using both conventional media, such as flashcards, real objects, and worksheets, as well as digital platforms, including PowerPoint, YouTube, Canva, Quizizz, and Wordwall. Nevertheless, they faced challenges such as facilities, time constraints, and technical difficulties. To overcome these challenges, they employed strategies that included preparing alternative media, practising beforehand, and seeking feedback from peers or lecturers. In conclusion, the study emphasizes that effective selection and preparation of teaching media not only improve microteaching practices but also demonstrate pre-service teachers’ professional readiness to adapt to real classroom contexts. The findings imply the need for more structured training and guidance from lecturers, greater creativity and experimentation among pre-service teachers, and further research on the long-term impacts of teaching media use.